METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PENDIDIKAN DASAR DAN MENENGAH - Hayumi; Nurussofi Hamalatil Jannah; Sofwatillah Amin (Desanta Publisher, 2025)
Islamic religious education (PAI) is one of the curricula that must be taught in schools from elementary education to higher education. The legality is stated in the Law and National Education System No. 20 of 2003 concerning the National Education System (UUSISDIKNAS) Chapter II, Article 30 paragraphs (1), (2) and (3), which aims to develop abilities, educate the life of the nation, have good morals, be capable, healthy, knowledgeable, responsible and become human beings who believe in and devote themselves to God Almighty. Methods or innovations in learning are needed by every teacher so that the atmosphere in teaching and learning in the classroom is not boring. There are so many methods that can be done by every teacher in teaching in the classroom. This study uses a descriptive qualitative method, namely a data collection technique. The purpose of this study was to find out the situation of elementary and secondary school students in applying the.